2022
DOI: 10.1186/s12967-021-03222-5
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of long-term effects of transcranial pulse stimulation (TPS) on the human brain

Abstract: Background With the high spatial resolution and the potential to reach deep brain structures, ultrasound-based brain stimulation techniques offer new opportunities to non-invasively treat neurological and psychiatric disorders. However, little is known about long-term effects of ultrasound-based brain stimulation. Applying a longitudinal design, we comprehensively investigated neuromodulation induced by ultrasound brain stimulation to provide first sham-controlled evidence of long-term effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“…In conclusion, TPS can be included as an effective and safe add-on treatment for Alzheimer's disease. Even though the first studies (7,9,10), as well as our findings, show promising results, more research is needed, including long-term results in patients. Besides larger sham controlled trials, translational research on the mechanisms of action and effects on cerebral network physiology will be needed.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In conclusion, TPS can be included as an effective and safe add-on treatment for Alzheimer's disease. Even though the first studies (7,9,10), as well as our findings, show promising results, more research is needed, including long-term results in patients. Besides larger sham controlled trials, translational research on the mechanisms of action and effects on cerebral network physiology will be needed.…”
Section: Discussionmentioning
confidence: 66%
“…However, besides in healthy subjects ( 9 ), no AD placebo-controlled trial has been published for TPS. Furthermore, there is a lack of information about the real-world applicability, safety, and effects of other centers outside the pioneer center in Vienna.…”
Section: Introductionmentioning
confidence: 99%
“…The AG has been implicated in constructional processing [ 20 22 ], so a possible hypothesis is that because it is functionally more relevant in the VisNW than, e.g., the precuneus, network function decreased together with corresponding visuo-constructive capacities despite stimulation of the precuneus. Recently, TPS has been shown to induce long-term effects on functional and structural connectivity in connected network areas after stimulation of a somatosensory cortex area [ 23 ]. In a similar vein, Verhagen et al [ 24 ] reported that in macaques not only stimulated brain regions but also their closest connected neighboring areas show modulated activity patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Other pioneering patient investigations exist for depression [12], epilepsy [13] and Parkinson's (performed with an unfocused diagnostic system, [14]). The first structural changes induced by human ultrasound neuromodulation have also been published recently using the TPS technology [15,16]. With more than 60 clinical and research centers established, TPS, meanwhile, is the most widely used technology for human ultrasound neuromodulation.Compared to electromagnetic neuromodulation technologies such as Transcranial Magnetic Stimulation (TMS) or Transcranial Direct Current Stimulation (TDCS), ultrasound-based techniques possess two distinct advantages: (1) the targeting of stimulation foci does not depend on the intracerebral conductivity situation-which may grossly be changed due to brain pathology-and (2) ultrasound is not limited to cortical stimulation but is the first non-invasive technique which may precisely target deep areas of the human brain.…”
mentioning
confidence: 99%
“…Other pioneering patient investigations exist for depression [ 12 ], epilepsy [ 13 ] and Parkinson’s (performed with an unfocused diagnostic system, [ 14 ]). The first structural changes induced by human ultrasound neuromodulation have also been published recently using the TPS technology [ 15 , 16 ]. With more than 60 clinical and research centers established, TPS, meanwhile, is the most widely used technology for human ultrasound neuromodulation.…”
mentioning
confidence: 99%